2016
DOI: 10.1016/j.jlumin.2015.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Green luminescence from Cu-diffused LiGaO2 crystals

Abstract: An intense green luminescence is observed from single crystals of LiGaO 2 doped with copper. Czochralski-grown undoped crystals are wrapped in thin copper foil and then held at 900 °C for 1 h in a flowing nitrogen atmosphere. Large concentrations of Cu + ions enter the crystals during this process and occupy Li + sites. These copper-diffused crystals are characterized with optical absorption, photoluminescence (PL), photoluminescence excitation (PLE), thermoluminescence (TL), and electron paramagnetic resonanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Alloying of LiGaO2 with ZnO creates a material with a band gap tunable in 3.3e5.6 eV range [10]. Besides when doped with cupper ions this crystal was studied as a material for optically and thermally stim-ulated dosimetry [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alloying of LiGaO2 with ZnO creates a material with a band gap tunable in 3.3e5.6 eV range [10]. Besides when doped with cupper ions this crystal was studied as a material for optically and thermally stim-ulated dosimetry [11].…”
Section: Introductionmentioning
confidence: 99%
“…Though many potential applications of LiGaO2 imply use of its optical properties there are not many studies of its luminescence characteristics. As to our knowledge, there are some works devoted to luminescence of dopants in LiGaO2, such as ions of Cr 3 þ [18,19], Cu þ [11], V 3 þ [4], but very few studies deal with luminescence of pure crystals e among them the early work of Dirksen [15], where the observed emission band at 360 nm and its excitation band at 220 nm were explained by charge transfer transitions between Ga and O ions, and the recent work [20] on luminescence of LiGaO2 nanoflakes with the same interpretation of the emission and excitation bands, located at lower energies compared to bulk crystal.…”
Section: Introductionmentioning
confidence: 99%
“…The first reported β-LiGaO 2 -based phosphor was β-LiGaO 2 :Fe 3+ , which emits deep red light near 740 nm [47]. Later studies reported β-LiGaO 2 :Cr 4+ [48] and β-LiGaO 2 :V 3+ [49], which respectively exhibited near-IR fluorescence near 1250 and 1700 nm, and β-LiGaO 2 :Cu + [50], which exhibited green fluorescence near 520 nm. Because the β-LiGaO 2 :Fe 3+ phosphor has a high internal quantum efficiency of ∼80% [47,51], it has recently received attention again as a red phosphor in solar simulators [51].…”
Section: β-Ligaomentioning
confidence: 99%
“…[35,36] TL or TSL has been widely applied for measuring deep and relatively shallow traps in optical and photonic materials [37,38] and has been quite useful for optical studies of single crystals, films, phosphors, and transparent ceramics for lasers, scintillators, and solid-state lighting applications and more. [9,[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] However, its applications in semiconductors has not been realized until recently [5,8,54] and are still very limited. The goal of this article is to explain the basics of TL, inform the reader about its capability as a great tool for measuring the energy levels of donors and acceptors in semiconductors, and bring the attention to the development of cryogenic thermally stimulated photoemission spectroscopy (C-TSPS) [55] which extends TL or thermally stimulated emission measurements to cover the entire range of shallow and deep levels in bandgap materials.…”
Section: Introductionmentioning
confidence: 99%